Analysis of aerobic endurance capacity level and body mass index of safin pati sports school soccer players born in 2006 - Fathurizqon, Muhammad; Anam, Khoiril; Setiowati, Anies; Indardi, Nanang (Departement of Sports Coaching, Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2025)
Coaches have difficulty identifying players' aerobic endurance capabilities based on their body proportions. The purpose of this study was to determine the level of aerobic endurance capacity and the ideal body condition of Safin Pati Sports School soccer players born in 2006. The analysis presented in the form of a classification and through a research approach based on a quantitative descriptive approach.(Allsabah, 2021). The quantitative approach to data measurement is quantitative and the statistics are objective using calculations from predetermined samples. The method in this study is a quantitative descriptive sampling method using purposive sampling and the analysis method uses quantitative descriptive statistics. Participants in this study were Safin Pati Sports School soccer students born in 2006. The sample consisted of 22 students out of 26 students who met the criteria, 4 of whom had injuries. The measurement tests used were Multistage Fitness Test, weighing and measuring height. The results of the study showed that the level of aerobic endurance capacity of Safin Pati Sports School soccer students averaged a value of 49.7 in the excellent category and the average player's body mass index value was 20.49 in the normal category. The conclusion from the results obtained from this study is that those who have excellent endurance are 82%, those who have good endurance are 14%, and those who have sufficient endurance are 5%. While the body mass index value of players in the underweight category is 14% and in the normal category is 86%. Coaches must maintain the level of aerobic endurance capacity and body mass index values they have and continue to pay attention to the training program with the food intake received by their players.